The unreliability of egocentric bias across self–other and memory–belief distinctions in the Sandbox Task. Issue 11 (7th November 2018) - Samuel, Steven; Legg, Edward W.; Lurz, Robert; Clayton, Nicola S.
Abstract : Humans are often considered egocentric creatures, particularly (and ironically) when we are supposed to take another person's perspective over our own (i.e. when we use our theory of mind). We investigated the underlying causes of this phenomenon. We gave young adult participants a false belief task (Sandbox Task) in which objects were first hidden at one location by a protagonist and then moved to a second location within the same space but in the protagonist's absence. Participants were asked to indicate either where the protagonist remembered the item to be (reasoning about another's memory), believed it to be (reasoning about another's false belief), or where the protagonist would look for it (action prediction of another based on false belief). The distance away from Location A (the original one) towards Location B (the new location) was our measure of egocentric bias. We found no evidence that egocentric bias varied according to reasoning type, and no evidence that participants actually were more biased when reasoning about another person than when simply recalling the first location from memory. We conclude that the Sandbox Task paradigm may not be sensitive enough to draw out consistent effects related to mental state reasoning in young adults.